Magneto-optically active magnetoplasmonic graphene. Issue 43 (28th April 2017) - Lee, Jaewook; Lee, Jaebeom
Abstract : Two-dimensional nanocomposites with magnetic and optical properties were investigated for novel magneto-optical (MO) applications. Abstract : Two-dimensional nanocomposites with magnetic and optical properties were investigated for novel magneto-optical (MO) applications. Such an MO effect could be induced and enhanced by synergistic properties with magnetic and plasmonic coupling. In this study, magnetoplasmonic graphene (MPGRP) decorated with Au nanoparticles (NPs) and magnetic NPs (MNPs) was simply prepared as a 2D MO active material. This MPGRP exhibited superparamagnetic behaviour at room temperature and strong MO activity, resulting from magnetic spin from the MNPs and electron spin from the Au NPs on one graphene sheet, which is beneficial for memory or optoelectronic devices, sensing platforms, energy harvesting, and biomedical MO devices.